Phraseological Units in V. Vysotsky's Poetry (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Vladimir Vysotsky, a renowned Russian poet, singer, and actor, is known for his unique and deeply expressive poetry, which reflects the complexities of life in the Soviet era. His works often intertwine personal experiences with social and political issues. One of the significant features of Vysotsky's poetic language is his use of phraseological units, which enhance the emotional impact and depth of his works. This article examines the role and function of phraseological units in Vysotsky's poetry, analyzing how they contribute to the formation of imagery, character development, and thematic exploration. Vysotsky often uses idiomatic expressions, proverbs, and colloquial phrases to reflect the common speech of his time, while simultaneously imparting a sense of universal truths and emotional intensity. These phraseological units not only preserve the authenticity of everyday language but also serve as a tool for conveying deeper meanings, adding irony, humor, or pathos to his poems. Through this analysis, the article aims to demonstrate the centrality of phraseological units in shaping Vysotsky's distinct poetic style and his ability to communicate complex emotional states and social realities.